The Potential Return on Investment of the Recruitment Strategies for an Academic Unit Focused on Agricultural Sciences - J. Tanner Robertson; Taylor Hurst; Kevin Williams; Lance Kieth (Journal of Applied Communications, 2017)
University recruitment strategies could be an important factor in attracting students and keeping enrollment numbers growing to a desired level. Research has shown that colleges of agriculture should investigate their traditional recruiting techniques and develop new plans to target desirable students. Students are viewed as revenue generators for the university, and with money and time being two important considerations, it is essential and helpful to know where both are best utilized in the recruitment process. The purpose of this study was to determine which recruiting methods and strategies are the most cost effective and work best for agriculturally focused departments. The researchers used a descriptive survey to collect data on participants’ preferred and influential recruitment methods and strategies. First-year students in this study chose campus tours and visiting with a faculty member on campus to be the most influential over all other recruiting strategies/methods in their decision to enroll at the university. Additionally, these specific recruitment strategies are also least expensive to employ, therefore, giving the department/university over 15 times the return of its investment. Promotional materials such as caps, key chains, and pens can produce a very high return because of the low input cost per unit. Overall, the strategies the department employs to recruit prospective students show to be effective, however, there is always room for improvement. However, other factors such as scholarship availability, cost of tuition, admission requirements and proximity to home could also be what attract students to the university.
Keywords: College Choice; Marketing; Recruitment Strategies; Return on Investment